2020
DOI: 10.1542/peds.2019-1121
|View full text |Cite
|
Sign up to set email alerts
|

STEPP IN: Working Together to Keep Infants Warm in the Perioperative Period

Abstract: OBJECTIVES: Reduce postoperative hypothermia by up to 50% over a 12-month period in children's hospital NICUs and identify specific clinical practices that impact success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 25 publications
(8 reference statements)
0
19
0
Order By: Relevance
“…Axillary temperature, which is commonly used in NICUs [14] and in PACUs [70] is close to core temperature, at least in normal temperature ranges, but not as accurate. This When oesophageal monitoring is not feasible, e.g., due to surgical procedure, nasopharyngeal temperature is an adequate alternative and a reliable surrogate for core temperature [58,66].…”
Section: Other Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Axillary temperature, which is commonly used in NICUs [14] and in PACUs [70] is close to core temperature, at least in normal temperature ranges, but not as accurate. This When oesophageal monitoring is not feasible, e.g., due to surgical procedure, nasopharyngeal temperature is an adequate alternative and a reliable surrogate for core temperature [58,66].…”
Section: Other Sitesmentioning
confidence: 99%
“…On the other hand, some studies demonstrate that with an adequate protocol, hypothermia rates can be below 10% [ 14 , 15 , 16 , 17 ], even in preterm infants [ 18 ]. Thus, it seems that the rate of perioperative hypothermia depends more on the actual warming strategy, and less on patient factors, regardless of age or surgical procedure.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the Children’s Hospitals Neonatal Consortium STEPP-IN initiative published results showing that a multi-institutional quality improvement project reduced postoperative hypothermia from 20.3% to 10.5%. 16 However, no studies have demonstrated sustained improvement below 10%. We aimed to reduce the percentage of postoperative temperatures <36°C in NICU patients from 10% to 6%, an approximately 40% reduction, over 6 months from May 1 to November 30, 2017, and sustain for 6 months, until May 1, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…At the time, we noted that NICU patients at our institution were also having a relatively higher incidence of perioperative hypothermia at 44% as compared to the average national rate reported by the Children’s Hospital Neonatal Consortium of approximately 20.3%. 21 …”
Section: Introductionmentioning
confidence: 99%